EFEKTIVITAS PEMBELAJARAN DAN LAYANAN KLASIKAL DALAM MENGEMBANGKAN ASPEK KOGNITIF PESERTA DIDIK KELAS I–III SEKOLAH DASAR 137 PALEMBANG - Wolly Dewa Liandra; Henni Riyanti; Nadya Syafwa Salsabila; Enjang Kurnia; Suci Novita Astina; Siti Sholehah; Rohamatul Nur Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of classical learning and services in developing the cognitive aspects of students in grades I–III at SD Negeri 137 Palembang. This study uses a descriptive qualitative approach with data collection techniques through observation, documentation, and field notes. The research subjects consisted of students in grades I, II, and III. The results showed that students' cognitive development differed at each grade level. Students in grade I have fairly good attention and memory skills, but still experience difficulties in reading and expressing opinions. Students in grade II show a decrease in learning focus and difficulty in understanding instructions and thinking logically. Meanwhile, students in grade III begin to experience improvements in reading skills, but are still slow in reasoning and understanding information. Classical learning and services play a role in supporting students' cognitive development, although the results are not optimal.